Diseño de control y simulación de un sistema de generación de energía eléctrica basada en módulos fotovoltaicos, un inversor trifásico conectado a la red y baterías como unidad de almacenamiento - Paredes Peñaherrera, Ricardo (2011)
The project involves the design of controller and simulation of a system of power generation based on photovoltaic panels. The system consists of the following components: photovoltaic panels, which convert solar energy into electricity. The output of the panel system is connected boost converter that regulates and filters the DC voltage delivered by the DC-Link to the arrangement of panels about 520VDC to 200VDC (depending on MPPT), this converter uses a high frequency transformer in order to produce insulation. Fed DC-link DC-DC converter for battery charging BUCK, and also connects a three-phase inverter which provides power to the connected three-phase network. It should be noted that our project will not be implemented physically. The project is based only on simulations and calculations.